ANALISIS PENGARUH PRAKTIK PENGHINDARAN PAJAK TERHADAP NILAI PERUSAHAAN: TRANSPARANSI INFORMASI SEBAGAI VARIABEL PEMODERASI - Istiharoh Nadia Hanif; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effect of tax avoidance on the firm value  with transparency of information as the moderating variable. The independent variable that is used in this research is tax avoidance which is measured by Book Tax Difference (BTD) and Cash Effective Tax Rate (Cash_ETR). Variables dependent are firm value which is measured by Tobin’s Q. Then moderating variable is transparency of information which is measured by 68 voluntary disclosure index. The population consist of manufacturing companies listed on Indonesia Stock Exchange during 2015-2017. Samples are selected using purposive sampling method and acquired 184 companies during 3 years. Test analysis using multiple regression model. Finding in this study indicates that tax avoidance with BTD proxy has a significant negative effect to the firm value. Then the transparency of information also strengthens the relationship between tax avoidance with BTD proxy and the firm value.